The use of effective microorganisms changed the soil microbiota of canals in Maricá city, Brazil (Acta Scientiarum. Biological Sciences, 2023)
The objective of this study was to evaluate the effect of bioremediation, through the application of two different strategies of effective microorganisms as treatment of effluents in the parameters of water quality and in the bacteriological profile of the soil of ‘Canal da Cidade’ - Maricá, Rio de Janeiro, Brazil. The metagenomic analyzes indicated that the abundance and richness of microorganisms in the substrate increased significantly after the bioremediation strategy used in this study. Because of bioremediation, 31 bacterial species disappeared from the environment when comparing the initial and final bacterial profiles of the soil, where 94% of these 31 species were anaerobic. Furthermore, 61 new aerobic or facultative aerobic species appeared in the channel substrate after bioremediation. As a consequence of bioremediation, the dissolved oxygen concentration and pH values increased significantly throughout the bioremediation process, indicating that the changes found in the microbiological profile of the soil contributed to the improvement of water quality parameters, helping the environment to move from anaerobic to aerobic characteristics. Thus, it is possible to state that the use of effective microorganisms directly affected the physical-chemical parameters of water quality and the microbial profile of the soil community of ‘Canal da Cidade’.